Cognitive theories on decision making: among reason, emotions and social context - Chaverri Chaves, Pablo (2023)
This article makes a general exploration of some of the most prominent decision-making theories in the sociocognitive field, with the purpose of providing analysis that serves to clarify the characteristics of decision-making and the way in which various elements influence it. To do this, it begins by contextualizing the theory about decision-making, then three theories are described in this regard: rational theory, bounded theory, and ecological theory. Next, the way in which socioeconomic status, culture, upbringing, reason, and emotion influence decisions is reviewed. Finally, it closes with a discussion of the rationality and potential of ecological theory to guide public decisions, as well as a thoughtful conclusion.